PENGARUH PENAMBAHAN ASTAXANTHIN PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENUR UDANG WINDU (Penaeus monodon) - T. Fajar Khairullah; Suri Purnama Febri; Hanisah Hanisah; Salamah Salamah (Jurnal Perikanan Unram, 2024)
Tiger prawns are a fishery commodity that has quite high economic value because tiger prawns taste delicious and tasty and their nutritional content is very high. The obstacles often faced in cultivation are slow growth and low survival of tiger prawn fry (Penaeus monodon), so this research aims to analyze the effect of adding astaxanthin to commercial feed on the growth and survival of tiger prawn fry (Penaeus monodon) and determine the best dose of astaxanthin. added to commercial feed can increase the growth and survival of tiger prawns (Penaeus monodon). The research method used was a Completely Randomized Design (CRD) with 4 treatments and 3 three replications. The treatments that will be carried out are: control, PA1 (150 g/ 1/2 kg feed), PA2 (250 g/ 1/2 kg feed) and PA3 (500 g/ 1/2 kg feed). Parameters observed: Absolute Length Growth, Absolute Weight Growth, Daily Growth Rate, Survival rate (SR), Feed Efficiency and Feed Conversion Ratio. The results of this research show that the best effect of Astaxanthin in commercial feed for the growth of tiger prawns is in the PA2 treatment (addition of astaxanthin at a dose of 250 g). Keywords: astaxanthin, growth, survival rate, tiger prawns